(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The hedonic lifestyle, brand image, and product knowledge are aspects that are thought to influence purchasing decisions. The purpose of this study was to determine the effect of a hedonic lifestyle, brand image, and product knowledge on purchasing decisions for Samsung brand smartphones in Denpasar City. The sample size was determined 10 times the number of indicators so that a sample of 150 respondents was obtained. The sampling technique used is purposive sampling. To test the hypothesis is done with multiple linear regression. From the results of the analysis it can be concluded that: 1) hedonic lifestyle has a significant effect on purchasing decisions, 2) brand image has a significant effect on purchasing decisions, 3) product knowledge has a significant effect on purchasing decisions, 4) hedonic lifestyle, brand image, and product knowledge have a significant effect on purchasing decisions.